2015
DOI: 10.11113/jt.v77.6053
|View full text |Cite
|
Sign up to set email alerts
|

Digital Ritualized Interaction: Towards Conceptualizing Mediated Familial Bonding via Family Connecting Technology

Abstract: Appropriation of connecting technology in the context of family use has revealed its affordance as mediating tool to facilitate familial bonding, as that which is beyond communication. Yet, its operationalization through the HCI design is still not extensively studied. It is postulated that the theory of Interaction Ritual and family ritual could serve as a lens for understanding of how interface design mediates such bonding in digital environment. As theories, they are specifically tailored to understanding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, women are still largely responsible for kinkeeping or maintaining contact and communication with family members in the digital age. In their study of Malaysian WhatsApp users, Kamal et al (2016) found that women were still largely responsible for kinkeeping by facilitating communication and keeping conversations going. It may be that the nature of kinkeeping does not change in technological settings and therefore women may be more likely to find social media with extended family members in more positive terms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women are still largely responsible for kinkeeping or maintaining contact and communication with family members in the digital age. In their study of Malaysian WhatsApp users, Kamal et al (2016) found that women were still largely responsible for kinkeeping by facilitating communication and keeping conversations going. It may be that the nature of kinkeeping does not change in technological settings and therefore women may be more likely to find social media with extended family members in more positive terms.…”
Section: Discussionmentioning
confidence: 99%